Magnetic resonance imaging in rhino-orbital-cerebral mucormycosis - Kanduri Sreshta (Indian Journal of Ophthalmology, 2021)
Coronavirus disease-associated mucormycosis (CAM) is an established clinical entity in India. In the past 4 months, there has been a sharp upsurge in the number of CAM cases in most parts of the country. Early diagnosis can be lifesaving. Magnetic resonance imaging (MRI) imaging remains the corner stone of management in patients with ROCM. This review discussed the utility of MRI imaging in ROCM with an emphasis on the ideal MRI protocol in a suspected case of ROCM, the pathways of spread of infection, the classic diagnostic features, MRI for staging of the disease, MRI for prognostication, MRI for follow up, and imaging features of common differentials in ROCM. The pit falls of MRI imaging and a comparison of CT and MRI imaging in ROCM are discussed. The clinical interpretation of areas of contrast uptake and those of necrosis and its relevance to treatment are discussed. This review aims to familiarize every member of the multidisciplinary team involved in managing these patients to be able to interpret the findings on MRI in ROCM.